2021
DOI: 10.3389/fphys.2021.670323
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Related Ratios Predict the 90-Day Outcome in Acute Ischemic Stroke Patients After Intravenous Thrombolysis

Abstract: Background and PurposeMounting researches have illuminated that the neutrophil-related ratios were related to the prognosis of acute ischemic stroke (AIS). However, few have compared their predictive value and accuracy. To make such comparison and identify the best indicator on the 90-day outcome, we investigated biomarkers including neutrophil ratio (Nr), neutrophil count (Nc), lymphocyte (L), neutrophil-to-lymphocyte ratio (NLR), platelet (P or PLT), platelet-to-neutrophil ratio (PNR), NLR-to-platelet ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The NLR as a marker of systemic inflammation is more responsive to clinical significance than neutrophils and lymphocytes alone, and it is useful ( 30 ), low cost, and widely used, thereby having excellent clinical potential. We assessed the diagnostic value of neutrophil percentage and NLR quintile for PSCI by ROC curves separately and found that the diagnostic accuracy was 58.3–59.0%; at the same time, the sensitivity and specificity were fair at 45.8–68.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR as a marker of systemic inflammation is more responsive to clinical significance than neutrophils and lymphocytes alone, and it is useful ( 30 ), low cost, and widely used, thereby having excellent clinical potential. We assessed the diagnostic value of neutrophil percentage and NLR quintile for PSCI by ROC curves separately and found that the diagnostic accuracy was 58.3–59.0%; at the same time, the sensitivity and specificity were fair at 45.8–68.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated leukocyte and neutrophil levels might release inflammatory mediators, such as proteases and reactive oxygen species, exacerbating brain tissue damage and edema 5 27. The increased number of neutrophil extracellular traps might also promote thrombosis and ultimately lead to EVT resistance 21.…”
Section: Discussionmentioning
confidence: 99%
“…All of the blood samples were collected before EVT. We documented neutrophil count (N),12 13 white blood cell count (W),13 eosinophil count (E),14 monocyte count (M),5 lymphocyte count (L),5 and platelet count (P/PLT),5 and calculated the following according to the above indicators: neutrophil to lymphocyte ratio (NLR),4 platelet to lymphocyte ratio (PLR),4 platelet to neutrophil ratio (PNR),5 6 platelet to white blood cell ratio (PWR)6, platelet to monocyte ratio (PMR),15 lymphocyte to monocyte ratio (LMR),16 monocyte to neutrophil ratio (MNR),5 eosinophil to lymphocyte ratio (ELR),17 and eosinophil to monocyte ratio (EMR) 18. NLR to platelet ratio (NLR/PLT) was calculated as the value of the ratio of NLR to platelets 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study ( Gao et al, 2021 ), investigated the neutrophil-related ratios in patients with acute ischemic stroke after thrombosis. After adjusting for confounders, they reported several granulocyte parameters were independently associated with 90-day outcomes.…”
Section: Introductionmentioning
confidence: 99%